In the flesh. [videorecording (DVD)] The complete season two - O'Hanlon, Jim; Newberry, Luke; Bevan, Emily; Cains, Harriet (Warner Home Video, 2014)
Kieren, a recovered zombie (Partially Diseased Syndrome (PDS) sufferer) is keeping his head down and squirreling money into his "escape fund" for Paris. But in the wider world, fear is in the air. With the arrival of new and explosive characters from both Victus and the ULA, Kieren's plans are thrown into disarray as both set their sights on him. As Kieren finds himself caught in the emotional crossfire, will he ever be able to live a quiet life?